The Role of the North Sumatra Provincial Public Order Agency in Regulating Street Children (Case Study in Kampung Lalang on the Border of Medan City and Deli Serdang Regency) - Dorowati, Butet; Adam, Adam; Batubara, Beby Masitho (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the role of the North Sumatra Provincial Civil Service Police Unit (Satpol PP) in controlling street children in the Kampung Lalang area, on the border between Medan City and Deli Serdang Regency, and to identify the obstacles encountered in its implementation. The research method used a qualitative approach with interview, observation, and documentation techniques. The research informants consisted of Satpol PP officials, relevant social agencies, and street children who were the objects of control. The results showed that the role of Satpol PP had been carried out based on Biddle's (1986) role theory, which includes normative, functional, coordinative, social expectation, and rehabilitative roles. Although the normative and coordinative roles were carried out quite well, the implementation of the rehabilitative and social roles was not optimal due to limited resources and weak cross-sector coordination. Internal obstacles included limited personnel, facilities, and budget, while external obstacles included family economic factors, low educational awareness, and a lack of guidance facilities. This study recommends strengthening the institutional capacity of Satpol PP, inter-agency synergy, and a child protection-based approach to enforcement.